Bis(2,6-dimethylpyridine-κN)gold(I) tetrachloridoaurate(III) - Ahmadi, Roya (International Union of Crystallography, 2008)
In the cation of the title compound, [Au(C(7)H(9)N)(2)][AuCl(4)], the Au(I) atom is two-coordinated in a linear arrangement by two N atoms from two 2,6-dimethylpyridine ligands. In the anion, the Au(III) atom has a virtually square-planar coordination geometry. The Au atoms both are located on centers of inversion. The crystal structure involves intermolecular C—H⋯Cl hydrogen bonds.